Pemikiran Nasaruddin Umar dan Henri Shalahuddin tentang Hadis Kesaksian Wanita: Sebuah Kajian Komparatif - Nurul Azizah (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to determine the differences in the interpretations of Nasaruddin Umar and Henri Salahuddin in understanding the hadith of women's testimonies. This study uses a qualitative type through literature study using the syarah hadith method and a comparative analysis approach. The results of the research and discussion show that the interpretations of women's testimonies are quite diverse, especially among Islamic feminists and traditional ulama. This study concludes that Nasaruddin Umar follows the feminist interpretation, and understands the hadith of women's testimonies contextually. Nasaruddin argues that reason is something that is universal, men and women have the same capacity in witnessing. Meanwhile, Henri Salahuddin in his normative interpretation follows classical scholars and understands the hadith of women's testimony tends to be textual. According to him, a woman has limitations in reason and religion so that the testimony of two women is equal to one man. This study recommends further research on the hadith of women's testimony with a social science approach.